Understanding Reference and Refrent in Everyday English Communication - Eva Febyana Sirait; Bernieke Anggita Ristia Damanik (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the role of reference and referent in everyday English communication through an empirical qualitative approach grounded in descriptive discourse analysis. The research examines naturally occurring spoken and written interactions containing personal, demonstrative, and definite reference forms to understand how referential expressions function within context-dependent communication. The findings reveal that personal reference predominantly operates through pronouns that enhance discourse efficiency by minimizing lexical repetition while maintaining referential continuity. Demonstrative reference is shown to depend heavily on shared contextual knowledge, situational cues, and interactional alignment between interlocutors, particularly in digitally mediated communication where contextual compression frequently increases interpretive ambiguity. Definite reference further demonstrates that successful communication relies on mutual cognitive accessibility and collaborative negotiation of meaning rather than solely grammatical structure. The study also identifies conversational repair and contextual inference as essential mechanisms for resolving referential ambiguity during interaction. These findings contribute to semantics and pragmatics by emphasizing that reference constitutes a dynamic interactional process shaped by discourse accessibility, common ground, and communicative cooperation in contemporary English communication environments.